Development of archeological information in the Departamento del Valle (1983)
Colombia has several characteristics that give it potential significance for understanding the development and dispersal of precolumbian culturale lementsand complexes. It is located at the «entrance» to South America linked by land with Central America. Thus, it is the first region to receive influences from the north, before passing them on to adjacent parts of thecontinent. It incorporates a variety of habitats but lacks the extremes of altitude and aridity that prevail in the Andean countries to the south. The intermontane valleys offer conditions similar to those of the eastern low lands, and the cordilleras are not formidable barriers to movement, facilitating adaptive radiation by precolumbian populations. Archeological investigations on the Caribbean coast have permitted reconstructing a sequence of pottery making groups that extends from about 3000 B-C to European contact. It has been suggested that the coastal river valleys and cienagas may have provided conditions favorable for the domestication of manioc and other tropical cultigens. The characteristics of the early archeological cultures and the environment have led many investigators to propose that Colombia was a major source of cultural innovations for Venezuela and Brazil throughout the precolumbian period.